Cytogenetic mechanisms of unisexuality in rock lizards - Spangenberg, Victor (Sci Rep, 2020)
Darevskia rock lizards is a unique complex taxa, including more than thirty species, seven of which are parthenogenetic. In mixed populations of Darevskia lizards, tri- and tetraploid forms can be found. The most important issues in the theory of reticulate evolution of Darevskia lizards are the origin of parthenogenetic species and their taxonomic position. However, there is little data on how meiosis proceeds in these species. The present work reports the complex results of cytogenetics in a diploid parthenogenetic species – D. unisexualis. Here we detail the meiotic prophase I progression and the specific features оf mitotic chromosomes organization. The stages of meiosis prophase I were investigated by immunocytochemical analysis of preparations obtained from isolated primary oocytes of D. unisexualis in comparison with maternal species D. raddei nairensis. It has been shown that in D. unisexualis at the leptotene-zygotene stages the axial elements and the synaptonemal complex (SC) form typical “bouquets”. At the pachytene-diplotene stage, 18 autosomal SC-bivalents and thickened asynapted sex Z and w univalents were observed. The presence of SYCP1 protein between the lateral elements of autosomal chromosomes proved the formation of assembled SCs. Comparative genomic hybridization (CGH) on the mitotic metaphase chromosomes of D. unisexualis was carried out using the genomic DNA isolated from the parental species D. raddei nairensis and D. valentini. In the pericentromeric regions of half of the mitotic chromosomes of D. unisexualis, specific regions inherited from maternal species have been found. Following our results, we suggest a model for diploid germ cells formation from diploid oocytes without premeiotic duplication of chromosomes in the oogenesis of diploid parthenogenetic lizards D. unisexualis. Taken as a whole, our findings confirm the hybrid nature of D. unisexualis and shed light on heterozygosity and automixis in diploid parthenogenetic forms.